The prokaryotic enhancer binding protein NTRC has an ATPase activity which is phosphorylation and DNA dependent. - Austin, S (1992)
The prokaryotic activator protein NTRC binds to enhancer-like elements and activates transcription in response to nitrogen limitation by catalysing open complex formation by sigma 54 RNA polymerase holoenzyme. Formation of open complexes requires the phosphorylated form of NTRC and the reaction is ATP dependent. We find that NTRC has an ATPase activity which is activated by phosphorylation and is strongly stimulated by the presence of DNA containing specific NTRC binding sites.